French Wisdom at the Serbian Medieval Court: Prov 31,1-9 as the Biblical Frame for the Portrait of Queen Helen of Anjou by Daniel II - Krstic, Darko (Théologiques)

(untitled) (Institut d’études religieuses de l’Université de Montréal, 2020)
Serbian Archbishop Daniel II (ca 1270-1337) described the Vitae of the medieval Serbian rulers from the Nemanjic dynasty. Among these royal hagio-biographies, the presentation of the life of Queen Helen of Anjou stands out since she is the only woman whose life was inspirational enough for Daniel II to incorporate it into the sequence of rulers and archbishops of medieval Serbia. In his picture of Queen Helen, Daniel II heavily employs various wisdom motifs from the Bible, especially from the Book of Proverbs. Prov 31,1-9 occupies a very prominent place as the background for Queen Helen’s long admonition to her sons and future kings, Dragutin and Milutin. Daniel II emphasizes the main point of the motherly admonition in Prov 31,1-9 - the just adjudication of deprived people - to suit the historical milieu of the Serbian court by underlining the importance of just judgment for Helen’s sons, the future kings. Nevertheless, at the same time, Daniel II does not develop a copy-paste reception of Prov 31,1-9 into his writing but consciously omits those elements of the instruction of Prov 31,1-9 (especially the warning against relationships with numerous women) which might appear to criticize the multiple marriages of King Milutin during his long reign (1282-1321).